The impact of earthquake preparedness training on mothers with physically disabled children: a randomized controlled study - Abdullah Adıyaman; Veysel Can; Abdullah Sarman (Scientific Reports)
Abstract This study aimed to evaluate the effect of earthquake preparedness training on the psychological resilience and earthquake preparedness levels of mothers with physically disabled children. The study was conducted at a special education and rehabilitation center in a province in eastern Turkey between January and April 2024, using a pre-test/post-test control group experimental design. A total of 78 mothers participated, with 39 randomly assigned to the experimental group and 39 to the control group. The experimental group received earthquake preparedness training. Data were analyzed using SPSS version 26. It was determined that 38.5% of the mothers in the experimental group were between 32–39 years of age, equal numbers of primary (35.9%) and secondary (35.9%) school graduates, 84.6% had nuclear families and 89.7% lived in urban areas. In the control group, 38.5% of the mothers were between 25–31 years of age, 33.3% were primary school graduates, 79.5% had nuclear families and 97.4% lived in urban areas. The experimental and control groups were similar in terms of baseline characteristics. Before the training, Adult Psychological Resilience Scale (APRS) scores were comparable between groups. After the training, the experimental group showed a significant increase in psychological resilience compared to the control group (p < .05). Similarly, Disaster Preparedness Scale (DPS) scores were comparable before the training, but the experimental group showed a significant increase in earthquake preparedness after the training (p < .05). The training enhanced both psychological resilience and earthquake preparedness in mothers, increasing their knowledge and awareness about earthquakes. Developing earthquake preparedness training and materials specifically for families with physically disabled children will contribute to the safety and well-being of both families and their children.